Assessment of factors associated with post-dialysis hyperglycemic spike and glycemic variability in patients undergoing maintenance haemodialysis - Yusof Khan, Abdul Hanif Khan; Zakaria, Nor Fadhlina; Zainal Abidin, Muhammad 'Adil; Kamaruddin, Nor Azmi (John Wiley & Sons, 2018)
Introduction: Chronic hyperglycemia and post-excursion hyperglycemia had been established as independent risk factors for diabetic complications. Recently, the concept of glycemic triumvirate, which encompasses chronic hyperglycemia, hypoglycemia and glycemic variability (GV) being favored as the main pathophysiology in diabetic outcome mainly cardiovascular complications. In Malaysia, cardiovascular disease attributed to one-third of all death in diabetic hemodialysis patients with a 3-fold increase in mortality as compared to non-diabetic patients. Objective: This study is performed to determine magnitude of post-dialysis rebound hyperglycemia, GV and their contributing factors. Methodology: 150 patients on haemodialysis were recruited, 93 patients had end-stage-diabetic-renal disease (DM-ESRD) and 57 patients had end-stage-non-diabetic renal disease (NDM-ESRD). Post-dialysis rebound hyperglycemia and GV indices (standard deviation [SD] and %co-variant [%CoV]) were obtained from 11-point and 7-point self-monitoring blood glucose (SMBG) profiles during hemodialysis day (HD) and non-hemodialysis day (NHD). GV were analysed between HD vs. NHD in DM-ESRD patients as well as those with NDM-ESRD. Results: Mean blood glucose during dialysis-day was 9.33 [SD 2.7, %CoV 30.6%] mmol/L in DM-ESRD compared to 6.07 [SD 0.85, %CoV 21.3%] mmol/L in NDM-ESRD (p =<0.01). Post-dialysis rebound hyperglycaemia occurred in 71% of patients (n=105. This spike was pronounced in DM-ESRD compared to NDM-ESRD (83.5% vs. 53.6%; OR 4.39 [95% CI 2.05 – 9.42]). Significantly higher GV indices were observed in DM-ESRD compared to NDM-ESRD during HD and NHD day especially in group with HbA1c 8-10% (p= <0.01). Furthermore, GV indices tended to be higher on HD compared to NHD (p= <0.01). Asymptomatic hypoglycemia was observed in 18% of patients (n=21), mostly during first-hour of hemodialysis. Higher HbA1c levels and older age were the main factors contributing to higher post-dialysis rebound hyperglycemia and GV and in this study (p<0.05). Correlation between HbA1c and mean blood glucose in this population is moderate with r2 = 0.58. Conclusion: Diabetic patients on haemodialysis are at increased risk of post-dialysis rebound hyperglycemia and fluctuations in blood glucose on hemodialysis-days with high HbA1c level and old age being two significant contributing factors. Since this group of patients are vulnerable to CVD mortality urgent attention is needed to rectify it.